Association between systemic inflammation response index trajectories and carotid atherosclerosis progression - You, Ningning; Su, Jing; Chen, Yi; Chen, Jun; Zhang, Jinshun (Frontiers in Endocrinology, 2025)
BackgroundThe systemic inflammation response index (SIRI) has emerged as a promising inflammatory biomarker linked to the onset and progression of cardiovascular disease (CVD). However, the association between initial and long-term trajectories of the SIRI index and carotid atherosclerosis (CAS) progression remains unexplored.MethodsThis longitudinal retrospective cohort study encompassed 11,623 adults undergoing multiple general health checks at Taizhou Hospital of Zhejiang Province from January 2017 to September 2024. SIRI values were derived using the formula: neutrophil count × monocyte count/lymphocyte count. To assess SIRI trends over time, latent class trajectory modeling was utilized. Hazard ratios (HRs) and 95% confidence intervals (CIs) for both the initial and trajectories of the SIRI index were determined through univariate and multivariate Cox proportional hazards analyses. Restricted cubic splines evaluated potential nonlinear associations between SIRI and CAS risk.ResultsOver a median follow-up of 2,043 days, 2,460 individuals experienced progression of CAS. After adjusting for conventional CVD risk factors, a 1-standard deviation (SD) rise in SIRI was linked to a 12% elevated risk of CAS progression (HR = 1.121, 95% CI 1.035–1.213). Comparable findings were noted when SIRI was stratified into quartiles. Participants were classified into three trajectory groups: low-stable, middle-stable, and high-stable. Following multivariate adjustments, the high-stable group exhibited a 1.166-fold increased risk of CAS progression (95% CI 1.021–1.333).ConclusionsElevated initial SIRI levels and a high-stable trajectory were associated with an increased risk of CAS progression. Tracking SIRI trends over time may help identify individuals at heightened risk, enabling more focused prevention and treatment strategies.